How to enhance generation Z users’ satisfaction experience with online fitness: a case study of fitness live streaming platforms - Meng Wang; Zheng Wang; Rong Deng (Frontiers in Computer Science)
With the rapid development of digital technology, online fitness live streaming platforms have become effective tools for helping users enhance their physical activity and health. However, the attitudes of Generation Z users, who form a significant portion of the platform’s user base, remain unclear. Identifying the factors influencing Generation Z’s use of these platforms and improving user satisfaction can assist in refining platform design and services, promoting sustainable development. A mixed-methods approach was employed to collect 1,788 user reviews, which were consolidated into 40 items. A questionnaire was then distributed to 314 respondents. In the first round, 165 open-ended questionnaires were distributed to identify specific influencing factors through factor analysis, leading to the development of a user experience evaluation scale. In the second round, 314 scale-based questionnaires were distributed, and structural equation modeling (SEM) was employed to explore the relationships between various factors and user satisfaction, resulting in the construction of a user satisfaction model. The factors influencing Generation Z users’ engagement with the platforms include social interaction, usefulness, convenience, functional quality, and technical quality. Among these, social interaction is the most critical factor affecting user satisfaction. Generation Z has unique needs regarding digital platforms. Therefore, platforms should provide services tailored to their psychological and behavioral characteristics, optimize business operation models, and further enhance the user experience.